Additively manufactured porous scaffolds by design for treatment of bone defects - Toosi, Shirin; Javid-Naderi, Mohammad Javad; Tamayol, Ali; Ebrahimzadeh, Mohammad Hossein; Yaghoubian, Sima; Mousavi Shaegh, Seyed Ali (Frontiers in Bioengineering and Biotechnology, 2024)
There has been increasing attention to produce porous scaffolds that mimic human bone properties for enhancement of tissue ingrowth, regeneration, and integration. Additive manufacturing (AM) technologies, i.e. three dimensional (3D) printing, have played a substantial role in engineering porous scaffolds for clinical applications owing to their high level of design and fabrication flexibility. To this end, this review article attempts to provide a detailed overview on the main design considerations of porous scaffolds such as permeability, adhesion, vascularization, and interfacial features and their interplay to affect bone regeneration and osseointegration. Physiology of bone regeneration was initially explained that was followed by analyzing the impacts of porosity, pore size, permeability and surface chemistry of porous scaffolds on bone regeneration in defects. Importantly, major 3D printing methods employed for fabrication of porous bone substitutes were also discussed. Advancements of MA technologies have allowed for the production of bone scaffolds with complex geometries in polymers, composites and metals with well-tailored architectural, mechanical, and mass transport features. In this way, a particular attention was devoted to reviewing 3D printed scaffolds with triply periodic minimal surface (TPMS) geometries that mimic the hierarchical structure of human bones. In overall, this review enlighten a design pathway to produce patient-specific 3D-printed bone substitutions with high regeneration and osseointegration capacity for repairing large bone defects.